Islamisation of Microfinance program in The Gambia - Saikou Gassama (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The Gambia is a 95 percent Muslim that is located in the western part of Africa. The population of the country is just around 2.5 m. The Gambia is largely dependent on Agriculture, tax and foreign aid and is ranked 178, in the Human Development Index 2019, the Gambia is classified as a country with medium human development. Currently there are various microfinance program that has been existing for years, but none of them are having Islamic microfinance loan products, as a result some did not take their loans and even those who take it is hard to change their lives, because it is purely for profit making and also the higher interest rate. Islamic Microfinance would be the best kind of development instrument for the population of Gambia. The microfinance institutions in the Gambia are very well expanded, they are the main source of credit to the Gambian population both rural and urban. Therefore it will be very important if microfinance institutions in the Gambia can introduce Islamic microfinance. The objective of this paper is to suggest ways to Islamize microfinance in The Gambia and the benefits Islamic microfinance. It is anticipated that the outcome of this paper would complement efforts by the government and NGO in the fight to eradicate poverty in the Gambia.